THE EFFECTIVENESS OF THE USE OF CRITICAL THINKING TECHNOLOGY - Zhumash A.M.,; Akbayeva G.M., (Scientific Journal of Pedagogy and Economics, 2020)
The article is devoted to the effectiveness of the use of critical thinking technology in the formation of the competence of future professionals. Future professionals must be able to analyze the ever-changing socio-economic processes, make and implement decisions appropriate to the conditions of market competition. The process of reforming the education system of the Republic of Kazakhstan is living in a new information technology era, associated with improving its content and quality, improving the National Model of education, the introduction of pedagogical technologies. Therefore, the training of specialists who have mastered new technologies is one of the most pressing problems today. In managing the educational process, the implementation of the professional and pedagogical culture of teachers and specialists requires that they be directed to special pedagogical, spiritual, highly humane, valuable goals. Each member of the teaching staff is a special organizer and implementer in a particular area of the educational process. Being a key figure in the educational process, if a specialist does not show his experience, knowledge, skills in fulfilling spiritual and cognitive needs, does not focus all his efforts on high goals, does not activate the organization of classes with intelligence, professionalism, everything will remain the same. Therefore, the introduction of critical thinking technology into the vocational training of future specialists through psychological reflective analysis and the identification of theoretical foundations justified in pedagogical practice makes the process of organizing education in a higher educational institution more effective. As a result, a future specialist who has mastered the technology of critical thinking: - be able to demonstrate the ability to professionally use critical thinking technology in his work; - be able to discuss the characteristic features of pedagogy and the shortcomings of teaching aids; - must form teaching methods based on critical thinking.